Analysis of Cutting Surface During Cutting of Electric Sheets - Spišák, E.; Kaščák, L.; Majerníková, J.; Džupon, M. (Проблемы прочности, 2017)
The contribution evaluates the influence of the size of the cutting gap on the quality of the cutting surface during the cutting process. Four types of electrical sheets were evaluated. Examined sheet types have the nominal thickness of 0.65 and 0.5 mm. Sheets differ in mechanical properties (yield strength, ultimate tensile strength, and elongation). For the impact analysis, four values of the 0.02, 0.05, 0.1, and 0.2 mm cutting gap were used.